2020
DOI: 10.3390/magnetochemistry6040052
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Magnetic Fields Induced Drug Release from Gold Coated Magnetic Nanoparticle Decorated Liposomes

Abstract: Magnetic nanoparticle-assisted drug release from liposomes is an important way to enhance the functionality/usefulness of liposomes. This work demonstrates an approach how to integrate magnetic nanoparticles with liposomes with the assistance of gold–thiol chemistry. The gold coated magnetic particles cover the thiolated liposomes from the outside, which removes the competition of the drug molecules and the triggering magnetic particles to free the inner space of the liposomes when compared to previous magneto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…These properties were used by Acharya and Chikan to enhance the functionality of drug-loaded liposomes made of DPPC/DSPC/Cholesterol-PEG-SH particles covered with gold-coated iron oxide NPs. The drug-release efficiency of these formulations under exposure to pulsed magnetic fields indicated that up to 20% of the drug can be released in a short time, compared to bare gold-covered or only iron oxide-coated liposome conjugates [ 180 ]. Except for SPIONs and gold NPs, Dai et al proposed hyperthermia-triggered local drug release by encapsulating responsive magnetic ammonium bicarbonate with Dox in liposomes with a particle size of about 210 nm.…”
Section: External Stimulus-responsive Liposomesmentioning
confidence: 99%
“…These properties were used by Acharya and Chikan to enhance the functionality of drug-loaded liposomes made of DPPC/DSPC/Cholesterol-PEG-SH particles covered with gold-coated iron oxide NPs. The drug-release efficiency of these formulations under exposure to pulsed magnetic fields indicated that up to 20% of the drug can be released in a short time, compared to bare gold-covered or only iron oxide-coated liposome conjugates [ 180 ]. Except for SPIONs and gold NPs, Dai et al proposed hyperthermia-triggered local drug release by encapsulating responsive magnetic ammonium bicarbonate with Dox in liposomes with a particle size of about 210 nm.…”
Section: External Stimulus-responsive Liposomesmentioning
confidence: 99%
“…These systems can be fabricated either through AMLs encapsulating core/shell magnetic/plasmonic nanoparticles [15], or through the incorporation of plasmonic and magnetic nanoparticles in different compartments of the liposomes (e.g. magnetic nanoparticles in the inner aqueous lumen and plasmonic nanoparticles bonded to the liposome surface) [28]. Figure 1 summarizes the main architectures of magnetoliposomes.…”
Section: Types Of Magnetoliposomesmentioning
confidence: 99%
“…The embedding of nanoparticles in the membrane surpasses AMLs limitations, as it enables the direct heating of the membrane, though the nanoparticle encapsulation efficiency is limited by the nanoparticle's size [22,30]. Although less explored, the nanoparticle-decorated magnetoliposomes make the entire inner cavity of liposomes available for drug loading and enables higher drug release efficiency/trigger [28], besides the potential use of sequential and complementary strategies (magnetic hyperthermia and photothermia). For example, Salvatore et al [27] developed magnetoliposomes comprised of iron oxide nanoparticles embedded in the membrane and bonded to the membrane surface through double-stranded DNA conjugated with a cholesteryl unit.…”
Section: Types Of Magnetoliposomesmentioning
confidence: 99%
See 1 more Smart Citation
“…3,[5][6][7][8][9][10] Because of these unique properties, g-Fe 2 O 3 NPs are used in magnetic resonance imaging (MRI) contrast enhancement, bio-magnetic separation, hyperthermia treatment and magnetic drug targeting, multi-terabyte storage, catalysis, biosensors, bio-separation, and thermoablation. [11][12][13][14][15][16][17][18] The most common method to synthesize colloidal g-Fe 2 O 3 NPs is the HI method. 19,20 In this technique, small amounts of precursor molecules are injected into a hot boiling solvent, which results in rapid decomposition of the molecular precursors thus producing inorganic nanomaterials (oxides, and semiconductors).…”
Section: Introductionmentioning
confidence: 99%